HUBUNGAN PENGETAHUAN TENTANG PENCEGAHAN PENYAKIT KUSTA DENGAN RISIKO PENULARAN KUSTA DI WILAYAH KERJA PUSKESMAS LOSARI, PUSKESMAS KEDATON DAN PUSKESMAS BABAKAN KABUPATEN CIREBON - Maryam Ulfah; Yani Kamasturyani; Putri Mutiara Ramandani (LPPM ITEKES Mahardika, 2018)
Background:Knowledge of leprosy prevention is the knowledge of a person doing a first line prevention or pervention action before a disease occurs. Based on data from Cirebon district Health OfficeThe incident of leprosy are 232 patients.According to the data primary health center Losari, Kedaton and Babakan There are 37 leprosy patients. Purpose: This research aimed to know an overview of knowledge about the prevention of leprosy, know an overview risk of cutaneous transmission, and knowlegde connection of prevention with leprosy transmission of primary health center Lossari, Kedaton and Babakan Cirebon District. Method:This is quantitative with Cross Sectional Study design. The population in this research is family members of leprosy primary health center Losari, Kedaton dan Babakan Cirebon district. The samples were choosen by Propotional Random Sampling which amounted to 114 respondents. The data retrieval research was conducted on 15 July – 15 September 2018. The research instrument was a questionnaire. Data analysis using Chi Square test. Result:The result of univariate analysis shows that connection of prevention leprosy was motsly good, that is mostly less 14 respondent (46,7%) and leprosy transmission mostly not risk 21 respondent (70,0%),. The result of chi square test was obtained p value = 0,011. Conclusion:Its indicatedthat there is a relationship betweenIndicating that H0 is rejected an Ha accepted means the a knowlegde connection of prevention with leprosy transmission of primary health center Lossari, Kedaton and Babakan Cirebon District